Pengaruh Lingkungan Fisik, Kualitas Pelayanan dan Fasilitas terhadap Kepuasan Konsumen Menginap di Duolos Phos Hotel Bintan - Hetty Yulianti Sihite; Fitriana Baitanu; Nensi Lapotulo (TOBA: Journal of Tourism, Hospitality, and Destination, 2025)
This study aims to analyze the influence of physical environment, service quality, and facilities on customer satisfaction at Doulos Phos The Ship Hotel, a heritage-themed accommodation shaped like a historic ship located in the Lagoi tourism area, Bintan. A quantitative approach was applied, using purposive sampling of 32 hotel guests who met the research criteria. The research instrument was validated and proven reliable (r-count > 0.349 and Cronbach Alpha > 0.80). The results of multiple linear regression analysis revealed that all three independent variables significantly influenced customer satisfaction, with the physical environment emerging as the most dominant factor (B = 0.352; Sig. = 0.003). These findings support the disconfirmation of expectations theory and are consistent with previous studies highlighting the role of physical atmosphere in shaping customer experience. Managerial implications include enhancing the hotel’s visual and historical elements, delivering empathetic and culturally aware service training, and improving digital facility innovations and public space comfort. This research contributes to the management of thematic accommodations by emphasizing multisensory experiences as a key driver of customer satisfaction in the hospitality industry.